Designing Standard Operating Procedures for International Classification of Diseases Coding: Merancang Prosedur Operasional Standar untuk Pengkodean Klasifikasi Penyakit Internasional - Putri, Putu Chrisdayanti Suada; Adiningsih, Luh Yulia; Santika, Komang Yuli; Para, Luh Gede Intan Prabayanti (Universitas Muhammadiyah Sidoarjo, 2025)
Every health service facility is required to organize electronic medical records (EMR) as an effort to improve the quality of service in accordance with the Minister of Health Regulation Number 24 of 2022 concerning Medical Records. Based on the preliminary study conducted by researchers at the North Denpasar II Health Center, the E-health center application has been used for patient registration. Officers have inputted diagnosis coding based on ICD 10 CM on the computer, but there is no SOP for filling in ICD 10 CM and ICD 9 CM codes in the EMR application. This study aims to analyze and design SOPs for filling in ICD 10 CM and ICD 9 CM coding in EMR. This type of research is descriptive qualitative research using a fishbone diagram by identifying Man, Money, Machine, Method, and Material. The results of the study from the Man aspect that implements the SOP are officers in the polyclinic and registration officers, Money namely there is Funding in training for filling in coding, Machine aspects, namely inputting ICD codes using computers, medical record applications/e-health centers and ICD code applications, Methods, namely there is a service flow for medical records and Material aspects used, namely patient registration files, personal health record books and E-health centers applications. The SOP for filling in ICD 10 CM and ICD 9 CM codes for the implementation of RME is designed according to the needs of Puskesmas II North Denpasar.